Interpretation of criteria for assessment of national heritage listing in Malaysia / Helena Aman Hashim - Helena, Aman Hashim (2017)
Cultural heritage is commonly protected internationally through a process of listing and gazettal. These properties which are listed cover a broad range of building types starting from the modest vernacular domestic housing to majestic government administration buildings. Countries with an established history of protecting cultural heritage in this manner provide criteria for listing which are accompanied by a set of guidelines to guide the assessment of cultural significance. These guidelines are necessary as although countries may appear to have similar criteria, their applications and interpretation are unique to each nation. In Malaysia, the criteria for listing National Heritage are provided under Section sixty-seven (67) of the National Heritage Act 2005. There are at present fifty-one (51) properties listed as National Heritage Buildings. The list comprises of many different of buildings types. Nevertheless, traditional Malay houses located in villages across the country and the ubiquitous traditional Chinese shophouse found at the core of Malaysia’s historic town centres are currently not listed on the National Heritage list. In addition, although Malaysia has proceeded to list properties, the government has not produced a set of guidelines that will ensure cultural significance is identified and assessed in a proper manner. Clear guidelines are necessary to mitigate potential disputes from owners when properties are selected for listing. Hence the objective of this research is to establish principles to guide assessment of cultural heritage for National Heritage listing for 7 out of the 9 criteria for National Heritage in the legislation. In addition, this research also seeks to establish principles to guide the assessment of the traditional Malay house and the traditional Chinese shophouse for National Heritage listing. The research is carried out in 2 stages and applies a qualitative research approach. In the initial stage, draft principles for assessment are identified from text rich semi-structured in-depth interviews with eleven (11) purposefully selected Malaysian heritage managers. The opinion of two 2 groups of experts, one Malaysian and the other international are then subsequently sought to validate these draft principles. Cross-group analysis is carried out on the responses from these 2 groups of experts to triangulate the data. New findings arising out of the experts’ groups were verified through established literature and World Heritage precedents. A total of forty-five (45) principles were formulated to guide assessment of the cultural heritage. In addition, seventeen (17) principles are explicitly identified to assess traditional Malay houses and another nine (9) principles for traditional Chinese shophouses. These principles comprise of factors that are involved in the process of assessment such as indicators of significance, considerations, explanatory notes and eligibility or ineligibility considerations. The results also showed that the uses of several criteria are potentially connected in an assessment. It is hoped that the development of these principles as a guide for assessment of cultural heritage for National Heritage listing will facilitate stakeholders involved in the related field both in Malaysia and the South-east Asian region.